UPDATING THE EDUCATIONAL STANDARDS OF WASATHIAH IN THE FIGHT AGAINST INTOLERANCE IN MADRASAH - A. Fatih Ghozali (Institut Agama Islam Depok Al-Karimiyah Sawangan Depok, 2024)
Madrasah has a strategic role in eliminating intolerance in Indonesia through the application of wasathiyah values, but madrasah does not yet have the concept, the wasathiya values to be applied, or the development of Wasathiyah Education. That is why this article aims to describe the concept, the types of wasathiyah values, and its development strategies. This writing uses the method of library research, i.e., digging up a wealth of data from various literature, both primary and secondary, which originates from books, journals, and other literature according to the focus of the study. According to some literature in results and discourse, education wasatiyyah is an education that promotes attitudes of tolerance, justice, and balance across all lines of life. The values of wasatiyyah to be updated in Madrasah are tawassut (midway), tawazun (balance), i'tidal (justice), tasamuh (tolerance), musawah (egaliter), syura (consultation), abhasah (reformation), alawiyat (priority), tahaddhur (civilization), wathaniyah wa muwathani (nation-state), and watiyah (inovatif). The model of development of education wasatiyyah that needs to be updated in madrasah is: first, madrasha must make a vision and mission that lead to the values of wasatiyya. Secondly, madrasahs should be able to develop a curriculum based on the values of wasatiyyah. Third, the strengthening of the habitation and culture of madrasah as a strategy for internalising the values of wasatiya Fourth, the madrasah should be able to strengthen Islamic moderation through programmes that integrate and lead to the values of the wasati.